2013
DOI: 10.4172/2469-4134.s1-001
|View full text |Cite
|
Sign up to set email alerts
|

Land Cover and Land Use Dynamics of Semi Arid Wetlands: A Case of Rumuruti (Kenya) and Malinda (Tanzania)

Abstract: In Sub-Saharan Africa, wetlands particularly those located in dry areas are intensively used and have caused significant loss of the wetlands and their riparian areas. The uses are intensified because of climate variability and the demand to feed the ever growing population. This paper presents results of assessment of land cover and use change in semi arid floodplains of Rumuruti and Malinda in Kenya and Tanzania respectively. Field survey, unsupervised classification and change vector analysis were used to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…This was attributed to the spatial resolution of the Landsat MSS used for 1976. Although other studies [64][65][66] reported high classification accuracies, there were challenges associated with the type of data used in these studies. In an attempt to avoid the issues of cloud cover as reported by Peter, et al [64], the use of SAR data set proved to be a solution as the sensor can penetrate through the cloud cover.…”
Section: Mapping Land-use and Land-cover Changes Impacts On Semi-arid And Arid Wetland Systems Using Freely Available Multispectral Imagementioning
confidence: 99%
See 1 more Smart Citation
“…This was attributed to the spatial resolution of the Landsat MSS used for 1976. Although other studies [64][65][66] reported high classification accuracies, there were challenges associated with the type of data used in these studies. In an attempt to avoid the issues of cloud cover as reported by Peter, et al [64], the use of SAR data set proved to be a solution as the sensor can penetrate through the cloud cover.…”
Section: Mapping Land-use and Land-cover Changes Impacts On Semi-arid And Arid Wetland Systems Using Freely Available Multispectral Imagementioning
confidence: 99%
“…The study reported an overall classification accuracy of 90%. Mwita, [66] utilized Landsat MSS, TM, ETM and ETM+ over a 30-year period with a sequence of 10 years to assess land-use and land-cover dynamics of the Rumuruti and Malindi wetlands in Kenya and Tanzania. The classification achieved an overall accuracy ranging between 88.28% and 95.17% for both wetlands.…”
Section: Mapping Land-use and Land-cover Changes Impacts On Semi-arid And Arid Wetland Systems Using Freely Available Multispectral Imagementioning
confidence: 99%
“…Wetlands provide the basis of human livelihoods in Africa through ecosystem services, for instance, the study done by Adekola et al (2012) described some of the provisioning services provided by wetlands to the livelihoods of local stakeholders, including monetary values for some services in rural areas of South Africa. Mwita (2013) highlighted that rural communities in Western Kenya depend on water from the Yala swamp for drinking, cooking, and washing purposes. Work by Marambanyika et al (2017) demonstrated the relevance of wetlands to rural livelihoods in rural Zimbabwe.…”
Section: Introductionmentioning
confidence: 99%
“…Wetlands in semi-arid regions particularly in developing countries are at high risk of degradation due to anthropogenic activities caused by the surrounding communities within their catchments. Furthermore, Land Use and Land Cover (LULC) changes and overexploitation of unsustainable resources' harvesting, urban development, industrial expansion and agricultural intensification in these wetlands contribute to the degradation of wetlands (Mwita, 2013). Lack of information about benefits derived from wetlands results in some wetlands being considered as wastelands.…”
Section: Introductionmentioning
confidence: 99%
“…According to their findings, alterations in vegetation and water body extents had exacerbated the Isimangaliso Wetland Park's dramatic decrease in recent years. In Kenya, remote sensing techniques have been used to assess land use and land cover change detection in Rumuruti [14], Nyando Wetland [15], Tana River Basin [16], and Ombeyi Wetland [17] among other large wetlands. These studies cumulatively indicated that the landscape of Kenya's wetlands is actively transforming due to human-induced factors.…”
Section: Introductionmentioning
confidence: 99%